Conditional dismissal as an alternative to the traditional criminal proceedings in Israel - Shoham, Efrat (Criminology & criminal justice, 2022)
The overloaded court system, along with the increasing recognition of the harm inflicted upon offenders by the criminal court procedure, led, in 2013, to the enactment of a new criminal-administrative procedure, termed “conditional dismissals,” which diverts minor offenses from the courts to be settled by prosecution authorities. This preliminary study examines the profile of 1750 cases of conditional dismissals concluded by district attorneys and police prosecution division between 2016 and 2018 and whether some notions of the “restorative justice” model were implemented. The findings indicate that both district attorneys and police prosecution division had initial difficulties in implementing the notion of diverting cases from the criminal court process. Over half of the cases in both agencies were for bodily injury and property offenses. There is a significant difference regarding the majority of the dismissal terms between the district attorneys and the police prosecution division. The results further indicate that 4.5% of all dismissals contained only restorative stipulations (especially in sex offenses), and one-third contained restorative stipulations along with punitive stipulations. The findings also show that the district attorneys are more inclined to use restorative terms, while the police prosecution division is more inclined to use punitive terms. The article discusses the possible explanations for these findings and the significant differences in the application of restorative practice between the police prosecution division and the district attorneys.